IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA SMP SUNAN GIRI MALANG - Maria Inna; Debora Rambu Newa; Rudy Setiawan; Muhammad Yusi Kamhar (Universitas Tribhuwana Tunggadewi, 2023)
The implementation of the Independent Curriculum (Kurikulum Merdeka) through the Project for Strengthening the Profile of Pancasila Students (P5) aims to bolster both student character and competence. This study aims to describe the implementation of P5 at SMP Sunan Giri Malang and analyze its contribution to students' mathematics learning motivation. Employing a qualitative approach with a descriptive case study design, data were collected through observation, in-depth interviews, and documentation. The results indicate that the P5 implementation under the